Efficacy of bisphosphonates in specific knee osteoarthritis subpopulations: protocol for an OA Trial Bank systematic review and individual patient data meta-analysis. Issue 12 (19th December 2018) - Deveza, Leticia A; Bierma-Zeinstra, Sita M A; van Spil, Willem Evert; Oo, Win Min; Saragiotto, Bruno T; Neogi, Tuhina; van Middelkoop, Marienke; Hunter, David J
Abstract : Introduction: Randomised clinical trials to date investigating the efficacy of bisphosphonates in knee osteoarthritis (OA) have found divergent results, with a recent meta-analysis finding no superiority of these drugs over placebo. Whether particular patient subgroups are more likely to benefit from this therapy than others is still unclear. We aim to investigate the effects of bisphosphonates compared with a control group (placebo, no treatment, another active treatment) on clinical and structural outcomes in specific knee OA subpopulations with possible distinct rates of subchondral bone turnover. Methods and analysis: Medline, Embase, Scopus, Web of Sciences and Cochrane Central Register of Controlled Trials will be searched from inception to February 2018. Randomised clinical trials will be eligible if they reported at least one potential treatment effect modifier at baseline: gender, menopausal status, age, body mass index, radiographic stage, knee pain severity, presence of bone marrow lesions, levels of biochemical markers of bone turnover (serum and/or urinary) and systemic bone mineral density status. Authors of original trials will be contacted to obtain individual patient data from each study. Risk of bias will be assessed using the Cochrane Collaboration's tool. The primary outcomes will include pain and radiographic joint space width loss. Studies using other MRI-based assessment of disease progression will also be eligible. Outcomes will be grouped into short-term (≤3 months), intermediate-term (>3 months; ≤12 months) and long-term (>12 months). Regression models will be used, adding an interaction term for each subgroup of interest to determine possible subgroup effects. There was no source of funding for this study. Ethics and dissemination: Dissemination of our findings is planned to occur through conference presentations, publication in peer-reviewed journals and social media. No formal ethics approval is generally required as no new data collection will be undertaken. PROSPERO registration number: CRD42018093327.